Retextualization as a didactic resource for text production - Bouzada, Cristiane de Paula; Faria, Marta Deysiane Alves; Silva, Adriana da (The ESPecialist, 2014)
Based on the conception of retextualization as a production of a new text from one or more base texts, we report in this article a writing activity in which public high school students retextualized the genre chronicle into other oral and written genres. The activity allowed students to work on linguistic, textual and discursive strategies from the base text and to project them into a new situation of interaction. The results suggest that it is a responsibility of formal education to create conditions for students to understand and take ownership of textual genres to become competent Portuguese Language users.